Changes in Plasma VEGF and PEDF Levels in Patients with Central Serous Chorioretinopathy - Michał Chrząszcz; Weronika Pociej-Marciak; Katarzyna Żuber-Łaskawiec; Bożena Romanowska-Dixon; Marek Sanak; Katarzyna Michalska-Małecka; Mojca Globočnik Petrovič; Izabella Karska-Basta (Medicina, 2021)
Background and Objectives: Retinal pigment epitheliopathy and hyperpermeability of choroidal vessels were postulated to be involved in the pathogenesis of central serous chorioretinopathy (CSC). Imbalanced levels of vascular endothelial growth factor (VEGF) and pigment-epithelium–derived factor (PEDF) were previously implicated in the development of chorioretinal diseases characterized by increased vascular permeability. We aimed to compare the plasma levels of proangiogenic VEGF and antiangiogenic PEDF for 26 patients with acute CSC, 26 patients with chronic CSC, and 19 controls. Materials and Methods: VEGF and PEDF levels were measured using a multiplex immunoassay or enzyme-linked immunosorbent assay. Correlations with disease duration were assessed. Results: VEGF levels differed between groups (p = 0.001). They were lower in patients with acute CSC (p = 0.042) and chronic CSC (p = 0.018) than in controls. PEDF levels were similar in all groups. The VEGF-to-PEDF ratio was lower in CSC patients than in controls (p = 0.04). A negative correlation with disease duration was noted only for PEDF levels in the group with chronic CSC (rho = −0.46, p = 0.017). Discussion: Our study confirmed that patients with CSC have imbalanced levels of VEGF and PEDF. This finding may have important implications for the pathogenesis of CSC. VEGF-independent arteriogenesis rather than angiogenesis may underlie vascular abnormalities in these patients.